Texto de estudio del idioma Kichwa para los niños de 2do, 3ro, 4to, 5to año de educación básica de las escuelas bilingües Domingo Faustino Sarmiento parroquia San Juan de Iluman cantón Otavalo y Bernardino Echeverría comunidad de Perafan parroquia de Imantag cantón Cotacachi provincia de Imbabura. - Cacuango Morán, María Juana (2013)
Ecuador is a country made ​​up of different nationalities each with its respective language and educational change, according to their geographical environment. Indigenous peoples have been characterized by the relationship and bond with the culture as it is embodied in knowledge, traditions and values. The struggle of indigenous people to keep alive the language, has gone through an extensive process, because there was no interest in preserving this expression. Over time it has come to understand the value of this language and transmit to future generations.